The Paradoxical Effect of Perceived Organizational Politics and Organizational Citizenship Behaviour - Faizal Susilo Hadi; Praptini Yulianti (Jurnal Dinamika Manajemen)
This study aims to explain how the psychological process affects perceived organizational politics (POP) toward organizational citizenship behaviour (OCB). The paradoxical effect of POP to OCB needs to be explained through two psychological processes: First, the mediation effect of psychological safety which explains POP as a barrier to OCB. Second, the mediation effect of careerism which explains POP as an OCB driver. One of the government institutions in Malang District used as research objects, involving 97 employees as respondents. A quantitative approach using Partial Least Square (PLS) used as the method of this study. The results showed careerism mediated the relationship between POP and OCB. But the surprising result is that psychological safety cannot mediate the effect of POP to OCB because employees feel that there is no high threat of doing voice behaviour, helping behaviour and individual initiatives in the political environment. These results indicate that OCB is a safe activity when it does not contrary to other people’s self-interest, so it does not cause a conflict.